Nutritional strategies in mitochondrial biogenesis and the performance effects of energy pathways for the Endurance athlete (Research, Society and Development, 2022)
Introduction: the need to provide and improve physical conditioning in high-performance sports, such as Endurance. shows the importance of debating on the improvement of mitochondrial biogenesis, together with nutritional strategies that aim to potentiate the requested energy pathway, in order to obtain excellent results, resulting in the improvement of physical conditioning in high-performance sports, such as Endurance. Objective: The present review aims to evaluate which nutritional strategies best benefit mitochondrial biogenesis to optimize the performance of energy pathways for the Endurance athlete. Methodology: The purpose of this research is descriptive. Results and Discussions: For the most efficient success and without loss of performance, the Endurance athlete needs nutritional strategies that fit the physiological needs of the individual. Nutrition should be used as a strategic tool to stimulate the recruitment and synthesis of mitochondrial proteins, with the increase in size, volume and number of mitochondria present in cells becoming an essential factor for the performance of energy pathways in Endurance athletes. Conclusion: nutritional factors exert a great influence on the performance of athletes in exercises, inducing the inflammatory response, damaging the antioxidant systems and increasing the production of reactive oxygen species (ROS) that can result in the possibility of the athlete to develop high performance activities such as Endurance.